Environmental Pollution Control Microbiology - McKinney, Ross E (CRC Press, 2009)
* Explains how bacteria bring about the stabilization of biodegradable organixc pollutants in various treatment environments * Discusses the proper environmental conditions for optimizing microbial stabilization * Shows how to acclimate recognize the limits between aerobic and anaerobic biological treatment systems * Demonstrates the easy calculations needed to determine the energy-synthesis relationships in the different biological treatment systems * Explores the microscope and simple laboratory tests that provide optimum operation of existing treatment plants